Use of Hydrophilic Monomers to Avoid Secondary Particle Nucleation in Miniemulsion Polymerizations of Methyl Methacrylate - Peixoto, Ana Cristina Bomfim; Campos, Izabella Maria Ferreira; Ferraz, Helen Conceição; Pinto, José Carlos (Journal of Research Updates in Polymer Science, 2016)
Miniemulsion polymerization is widely used to produce polymer nanoparticles. In many applications, it is important to ensure the narrow particle size distribution of the final product, which means that secondary micellar and homogeneous nucleation must be avoided during the reaction course. The present study proposes the use of hydrophilic comonomers to inhibit the occurrence of secondary particle nucleation in miniemulsion polymerizations of methyl methacrylate. Acrylic acid, metacrylic acid, 2-hydroxy ethyl methacrylate and methacrylamide were used as hydrophilic comonomers. It was observed that the use of small amounts of hydrophilic comonomers in miniemulsion polymerizations promoted by oil-soluble initiators could prevent secondary particle nucleation and lead to products with more homogeneous particle size distributions.